Analyzing Climate Change Debates in the U.S. Congress: Party Control and Mobilizing Networks. Issue 3 (September 2014) - Park, Hyung Sam; Liu, Xinsheng; Vedlitz, Arnold
<x xml:space="preserve">Abstract</x> This study examines the differences, if any, in congressional hearings and testimonies on global climate change between Democrat‐ and Republican‐controlled Congresses from 1976 to 2006. Using statistical and network analysis, we examine along party lines the connectedness among congressional committees, issue foci, and witness sectors. While the levels of attention to global climate change were similar between Democrat‐ and Republican‐controlled Congresses, our findings reveal that Democratic Congresses tend to seek scientific evidence for global climate change and advance energy‐regulatory policies with a focus on mobilizing environmentalists and scientific knowledge. In contrast, Republican Congresses tend to expand the climate change debates and conflicts by bringing in a diversified set of witnesses, focusing on the implications of international climate negotiations and economic impacts of policy changes, and mobilizing pro‐industrial sectors and non‐scientific opinions. Showing the differences in the networks that connect policy actors and mobilize various policy sources in congressional hearings and testimonies, we conclude that party control significantly affects the dynamics of climate change debates in the U.S. Congress for the given period.